On Palatalization as a Phonetic Process - Rankin, Robert L. (Kansas Working Papers in Linguistics, 1981)
The process usually labeled palatization of dentals or velars, which results in alveopalatal affricates in many languages, is seen to be the result of two separate phonetic developments, (1) change in place of articulation of the stop, and (2) change in manner of articulation of a following yod. Since labial stops do not undergo (1), the phonetic alterations subsumed under (2) can be clearly observed by examining the evolution of pj and bj clusters. Data are provided from several Romance languages to illustrate this evolution.